2009
DOI: 10.1007/s11661-008-9759-z
|View full text |Cite
|
Sign up to set email alerts
|

Composition Profiles around Solute-Lean, Spherical Nanocrystalline Precipitates in an Amorphous Matrix: Implications for Corrosion Resistance

Abstract: Although precipitates and the uneven solute distributions surrounding them are generally detrimental to the corrosion resistance of metals, solute-depleted nanocrystalline precipitates in an amorphous metallic matrix are unexpectedly benign. This good corrosion resistance might result from the beneficial effects related to solute buildup in the remaining amorphous matrix. In this work, we examine theoretically the influence of transformation strain, compositional strain, surface stress, capillarity, and alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…It should be noted that, as previously reported for similar materials, some nanocrystals are likely to be present in the amorphous forms of the material, however these were not directly observed in this work [16,17]. It has been suggested that such nanocrystals contribute to the good corrosion resistance of otherwise amorphous material [26].…”
Section: Microstructuresupporting
confidence: 45%
See 1 more Smart Citation
“…It should be noted that, as previously reported for similar materials, some nanocrystals are likely to be present in the amorphous forms of the material, however these were not directly observed in this work [16,17]. It has been suggested that such nanocrystals contribute to the good corrosion resistance of otherwise amorphous material [26].…”
Section: Microstructuresupporting
confidence: 45%
“…While such a dislocation based mechanism is unlikely to be active in the largely amorphous material used here, the possibility of an analogous sample preparation related mechanism warrants further investigation. Overall, the better corrosion resistance of the mainly amorphous form of the glass forming alloy, compared to the crystalline material, is attributed to the formation of a homogeneous single-phase solid solution [21,25,26]. The absence of surface heterogeneities such as segregation, dislocations, inclusions, grain boundaries as well as second phase precipitates, will not only reduce the possibility of galvanic cells and nucleation sites for corrosion but is also expected to enhance the stability of the passive films by decreasing the number of features that may result in passive film defects.…”
Section: Corrosionmentioning
confidence: 99%
“…The transition from pit initiation to metastable growth could be affected by the solute buildup around nanocrystals. 9,66 It is reasonable to conclude from the results shown here that the conditions for pit stability are similar for the fully amorphous and partially nanocrystalline variants of an Al-based glassy alloy. This result, combined with the measurement of pitting potentials that are significantly elevated over repassivation potentials, makes it possible to conclude that both pit initiation and propagation effects contribute to the good micrometerscale pitting resistance of the amorphous and partially nanocrystalline alloys relative to high-purity Al.…”
Section: Discussionmentioning
confidence: 53%
“…4,8 However, they differ from fully crystalline materials with nanometer-scale grain sizes in at least three respects: ͑i͒ isolated crystals embedded in an amorphous matrix lack grain boundary triple points with the associated defective structure, ͑ii͒ the remaining amorphous matrix surrounding a nanocrystal can collect slowly diffusing solute that is rejected from newly formed nanocrystals, 7 and ͑iii͒ the crystalline phase does not form a continuous path through the material. 9 A major concern for amorphous-nanocrystalline metallic glasses is the possibility that even partial devitrification compromises the superior resistance to pitting corrosion typical of the fully amorphous condition. The resulting chemical and structural heterogeneity may provide a location for pit initiation, as some secondary phases do in stainless steels and aluminum alloys, if it is less corrosionresistant than the surrounding matrix and above a critical size.…”
mentioning
confidence: 99%
“…Surface stress measurements have also been used to probe a wide variety of other phenomena including DNA hybridization, detection of antibodies in blood serum, and contraction of artificial molecular muscles . An understanding of surface stress has shed light in many other areas including thermal imaging with a bimetal oscillator, corrosion of certain composite materials, and structural transitions in thin magnetic films …”
Section: Introductionmentioning
confidence: 99%